Study of IL-35 Relation with Systemic Lupus Erythematous (SLE) and Effect Autoantibodies Because Disease - Ali, Noor abd al-Zahra; Ossama, Khawla Abdulkader; Ghaib, Amal Jabbar (American Journal of Biology and Natural Sciences, 2025)
Background; Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by the production of autoantibodies that target self-antigens. Interleukin-35 (IL-35) is a cytokine involved in immune regulation, and its potential role in SLE pathogenesis has gained attention in recent studies. Aims of the study; Investigate the relationship between Interleukin-35 (IL-35) levels and the presence of autoantibodies in patients with systemic lupus erythematosus (SLE), and to explore how IL-35 may contribute to the pathogenesis of the disease. Methodology; This study involved 176 SLE patients (132 females, 44 males) and 83 healthy controls (78 females, 5 males) from Al-Kafeel Hospital, Karbala, Iraq, from February 2 to October 10, 2024. IL-35 levels were measured using an ELISA kit, while autoantibodies were detected by chemiluminescent immunoassay (CLIA). Blood samples were processed and stored for analysis. Ethical approval and informed consent were obtained. Result; The demographic analysis revealed significant differences in gender distribution (P=0.0001) and age (P=0.0001) between patients and controls, with a higher proportion of females and patients over 50 years. Biomarker analysis showed significant increases in SSB-LA, ds-DNA, ANA, SS-A/Ro, and U1-SnRNP levels in patients compared to controls, with P-values ≤0.01. IL-35 levels showed no significant difference (P=0.124). No significant gender-based differences were observed, except for ANA. Age-related increases in ds-DNA, U1-SnRNP, and IL-35 were noted, with P-values of 0.0102, 0.049, and 0.019, respectively. Conclusions; The study highlights significant increases in autoantibodies (SSB-LA, ds-DNA, ANA, SS-A/Ro, and U1-SnRNP) in SLE patients, suggesting a strong immune response in disease pathogenesis. IL-35, however, did not show a distinct role, indicating potential complex immune interactions in SLE.